IMPROVING VOCABULARY MASTERY IN STUDENTS USING SHADOWING TECHNIQUES CLASS VII MTs. NURUL IMAN TELAGA JERNIH SECANGGANG ACADEMIC YEAR 2022 – 2023 - Rindiani Naransyahputri (Edelweiss : Journal Of Innovation In Educational Research, 2024)
The problem why students experience difficulties in following English lessons is a problem of the most basic abilities students do not have, namely their lack of mastery of English vocabulary.. This study aims to analyze the increase in vocabulary mastery related to verbs and demonstratives in class VII students of MTs. through the use of shadowing learning techniques. This research is a classroom action research. The subjects of this study were 24 class VII students with details of 18 boys and 6 girls. Data collection techniques using techniques quantitative descriptive. The results of the data analysis of the average score of students' vocabulary tests in cycle I were equal to50,83and the average score of students' vocabulary tests in cycle II is equal to61.25, meanwhile the average score of students' vocabulary tests in cycle III is equal to71.04. From cycle I to cycle III there was an increase of 20.21. So, student learning outcomes in vocabulary mastery related to verbs and demonstratives through the use of shadowing techniques in class VII MTs students increased. The research implication is that English teachers are expected to use shadowing learning techniques because it can improve vocabulary mastery related to verbs and demonstratives.